Resting autonomic nervous system activity is unrelated to antisocial behaviour dimensions in adolescents: cross-sectional findings from a European multi-centre study - Prätzlich, Martin; Kirchner, Marietta; Kieser, Meinhard (Journal of criminal justice, 2019)
Purpose - Autonomic nervous system (ANS) functioning has long been studied in relation to antisocial behaviour, but relevant measures (heart rate, heart rate variability, pre-ejection period, respiration rate) have rarely been considered together. This study investigated the relationship between these measures and antisocial behaviour. - Methods - Using a sample of 1010 youths with (47.8%) and without conduct disorder (52.2%) aged between 9 and 18years (659 females, 351 males, mean age=14.2years, SD=2.4), principal component analysis (PCA) was applied to various measures of psychopathology and antisocial behavior. Structural equation modelling was performed in order to test whether the ANS measures predicted PCA-dimensions. Cluster analysis was used in order to classify patterns of ANS activity. Analyses were performed separately for males/females and controlled for body-mass-index, age, caffeine use, cigarette smoking, sports, socioeconomic status, medication, cardiac problems. - Results - The PCA yielded three components: antisocial behaviour/comorbid psychopathology, narcissistic traits, and callous-unemotional traits. ANS measures were only weakly correlated with these components. Cluster analysis yielded high and low arousal clusters in both sexes. When controlling for covariates, all associations disappeared. - Conclusion - Our findings suggest that resting ANS measures are only weakly related to antisocial behaviour and indicate that smoking should be considered as an important covariate in future psychophysiological studies.
Gesehen am 17.01.2020